(untitled) (International Journal of Advanced Research in Computer Science, 2017)
There is developing interest for the product frameworks to perceive characters in PC framework when data is looked over paper archives as we realize that we have number of daily papers and books which are in printed arrange identified with various subjects. This procedure is likewise called document image analysis. To viably utilize Optical Character Recognition for character acknowledgment so as to perform Document Image Analysis, we are utilizing the data in Grid arrange. For document processing archive preparing we require a product framework called character recognition system. Along these lines the need is to create character acknowledgment programming framework to perform Document Image Analysis which changes records in paper organization to electronic arrangement. Now and then in this record handling we have to prepare the data that is identified with dialects other than the English. With the help of kohonen neural network training handwritten character recognition is also done. Keywords: perceive character, document image analysis, Grid arrange, electronic arrangement, neural network, handwritten character recognition.